Angle Class II malocclusion treated with extraction of permanent teeth - Barreto, Gustavo Mattos (FapUNIFESP (SciELO), 2013)
Angle Class II malocclusion associated with anterior open bite in adult patients demands a carefully elaborated orthodontic planning, aiming at restoring not only harmonious dental and facial esthetics, but also a balanced masticatory function. Orthognathic surgery or permanent teeth extraction are often the choice of treatment, therefore, treatment decision is related to all dental, skeletal and functional aspects. The present report discusses orthodontic compensation carried out by means of upper premolar extraction performed to correct the Class II canine relationship and, consequently, the anterior open bite, accepting that the upper incisors be retroclined. This clinical case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as part of the requirements for obtaining the BBO Certification. © 2013 Dental Press Journal of Orthodontics.
Keywords: Anterior open bite; Class II malocclusion; Orthodontic compensation